Cerebrospinal fluid and serum prealbumin (transthyretin) in patients with multiple sclerosis (MS): Comparison of particular subgroups of MS patients - Hybeľová, Mária; Svatoňová, Jana; Sobek, Ondřej; Adam, Pavel; Doležil, David; Adam, David (Folia microbiologica, 2009)
The levels of prealbumin (PAB, transthyretin) were determined and evaluated in the cerebrospinal fluid (CSF) and serum in various subgroups of the multiple sclerosis (MS) patients. In severely disabled patients, serum PAB was elevated more frequently. CSF and serum PAB concentrations were higher in treated than in nontreated patients; the values above the upper reference limits were also more frequently found in treated patients. PAB index showed a tendency to decrease during the course of the disease. The routine determination of PAB in CSF and serum is, therefore, recommended to be recognized in MS patients as a substantial clinical value and, thus, be comprised, including also immunoglobulins and other parameters, into the spectrum of characteristics in Protein Panel.
Keywords: stupeň závažnosti nemoci; Severity of Illness Index; Prealbumin; lidé; Humans; prealbumin; Male; mužské pohlaví; Multiple Sclerosis; roztroušená skleróza